Relationship between mitotic index and Ki67 expression in meningioma - Yusriany, Rini; Cangara, Muhammad Husni; Kaelan, Cahyono; Asyadi, Gunawan; Sungowati, Ni Ketut; Ihwan, Andi; Rosyidi, Rohadi Muhammad; Zainuddin, Andi Alfian (International Journal of Research in Medical Sciences, 2019)
Background: Meningioma is the most common primary central nervous system (CNS) tumor which covers 36.4% of all CNS tumors. Two important factors determining the prognosis of patients with a diagnosis of meningioma are the percentage of tumor resection and the degree of tumor histopathology. Because there are limitations to routine histopathological examination in predicting tumor progressivity, several examination techniques have been developed including cytogenetics and use of immunohistochemical examination. Method: Observational analytic study was carried out on 68 tumor samples in dr. Wahidin Sudirohusodo Hospital and the Makassar Pathology Diagnostic Center with diagnoses of meningioma from 2012-2018. The Sample size is determined by consecutive sampling method. Results: Sample Size were 68 people from Dr. Wahidin Sudirohusodo Hospital and the Makassar Pathology Diagnostic Center with diagnoses of meningioma which fulfilled the inclusion criteria and consisted of 19(27.9%) men and 49 (72.1%) women with an average age of 42 years. The most common location of the tumor was in the convexity area with an incidence of 29.4%. Grade I meningioma was found 41.2%, grade II of 32.4% and grade III of 26.5%. In grade I, the mean mitotic index was 0.25, grade II was (7.4) and grade III was 22.75. In grade I, the mean Ki67 expression was 1.01%. The highest expression was obtained in grade III with amean of 14.8% and the highest expression was 53%. The Spearman’s rho test results between the mitotic index and Ki67 expression show that there is a positive correlation of 0.490, which means that there is a moderate correlation. Conclusion: IHC expression of Ki67 increases proportionally to the degree of histopathology of meningioma. There is a positive correlation of 0.490 which means that there is a moderate correlation between the mitotic index and Ki67 expression.